In vitro anti-proliferative activity of alcoholic stem extract of Coscinium fenestratum in human colorectal cancer cells - ROJSANGA, PIYANUCH (D.A. Spandidos, 2010)
Coscinium fenestratum (Gaertn.) Colebr. is traditionally used for the treatment of cancer, arthritis and diabetes mellitus. The purpose of this study was to determine the molecular mechanisms by which this plant shows beneficial effects. An 80% ethanolic extract of C. fenestratum (80ET) was separated by its polarity into dichloromethane (DCM) and aqueous fractions (WF), and the anti-proliferative effects of 80ET, DCM and WF were investigated. Berberine, one of the major components of C. fenestratum, was used as a control. The 80ET, DCM, WF and berberine showed anti-proliferative activity as assessed by cell growth assay. Subsequently, the pro-apoptotic proteins NAG-1 and ATF3 were increased and the cell cycle protein cyclin D1 was decreased by the extract and its fractions. Interestingly, only the DCM fraction exhibited the induction of peroxisome proliferator-activated receptor γ (PPARγ) binding activity, which represents a pro-apoptotic activity in colorectal cancer cells. The overall results of this study indicate that the extract from this plant has anti-proliferative activity through the activation of pro-apoptotic proteins and PPARγ, and may have potential as a preventive regimen in the treatment of cancer.